Metode Sederhana untuk Mengendalikan Inverter 5-Tingkat Berbasis Algoritma ¼ λ - Leonardus Heru Pratomo (Jurnal Rekayasa Elektrika, 2019)
The inverter with low voltage harmonics on the output side is a very interesting topic, and widely studied. One of these solutions is a 5-levels inverter: Dual Buck DC-DC Converter - H Bridge Inverter (DBC-HBI). The inverter control methods based on digital sinusoidal pulse width modulation (DSPWM) are commonly implemented by one or a half of the wavelength algorithm (λ). However, one period could be constructed by combining four algorithms by ¼ λ. In this paper, an algorithm of DSPWM based on a ¼ λ algorithm is investigated. The aim of this research is the simplest control and capacities of memory. Finally, a verification of the proposed method was carried out by the experiment in the laboratory. Based on the laboratory tests: 1 λ algorithm has a simple algorithm, but uses large memory, whereas a ¼ λ algorithm more complicated but uses less memory.